2016
DOI: 10.1007/s00464-016-5011-x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of acute cholecystitis: a systematic review and pooled analysis

Abstract: Conservative treatment of acute calculous cholecystitis during index admission seems feasible and safe, especially in patients with mild disease. During long-term follow-up, less than a quarter of the patients appear to develop recurrent gallstone-related disease, although this outcome is based on limited data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 42 publications
4
47
0
9
Order By: Relevance
“…35,36 This group reported that about half the patients randomized to observation only eventually underwent cholecystectomy with most of the surgery performed for pain within the first five years after the initial hospitalization. The biliary-related mortality associated with conservative treatment is very low and is consistent with other reports 37,38 although this will depend upon the number of high-risk cases included in the conservative cohort.…”
Section: Discussionsupporting
confidence: 89%
“…35,36 This group reported that about half the patients randomized to observation only eventually underwent cholecystectomy with most of the surgery performed for pain within the first five years after the initial hospitalization. The biliary-related mortality associated with conservative treatment is very low and is consistent with other reports 37,38 although this will depend upon the number of high-risk cases included in the conservative cohort.…”
Section: Discussionsupporting
confidence: 89%
“…A prospective study of 42 elderly patients with acute cholecystitis and an APACHE-II score ≥ 12 showed that 7 patients (17%) suffered from ongoing sepsis, all of whom died [36] . In addition, since the gallbladder is left in situ, there is a chance of recurrent gallstone-related disease in at least 22% [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, la gran mayoría de cuadros en los que se podrían plantear estas alternativas requieren un diagnó stico de certeza, casi siempre mediante TC abdominopé lvica, que en el contexto actual debe inexorablemente extenderse al tó rax con el fin de descartar una infecció n por SARS-CoV-2 concomitante. Así, se podría plantear el tratamiento conservador de las apendicitis no complicadas asumiendo al menos 3-5 días de tratamiento antibió tico intravenoso y una tasa de recidivas en el primer añ o cercana al 30% 27 ; colecistitis agudas tambié n no complicadas, de nuevo asumiendo tasas de reingreso, fracaso terapé utico y cirugías má s complejas no desdeñ able 28,29 ; finalmente, considerar ampliar el espectro del manejo conservador en ré gimen extrahospitalario (en combinació n con un eventual drenaje percutá neo si fuese necesario) en estadios má s avanzados de diverticulitis aguda, siempre con foco inflamatorio local 30 , si bien no existe evidencia científica só lida que permita realizar de forma firme esta afirmació n. La consideració n de ampliar las indicaciones de realizar colecistostomías percutá neas podría estar justificado en pacientes COVID-19 durante la pandemia debido a la posibilidad de agravar el cuadro respiratorio así como a la posibilidad de estar recibiendo tratamiento anticoagulante debido a la alta incidencia de tromboembolismos pulmonares en estos pacientes 31,32 .…”
Section: Implicaciones Sobre Las Indicaciones Habituales En Cirugía Dunclassified